NUTRIENT UPTAKE AND ECONOMICS OF COTTON IN HIGH DENSITY PLANTING SYSTEM UNDER VARIED PLANT SPACING AND NITROGEN LEVELS - S. BHARATHI (The Journal of Research ANGRAU, 2018)
The experiment was conducted during Kharif, 2016 - 2017 to determine the optimum spacing and nitrogen in cotton under high density planting system. A closer spacing of 60 cm × 10 cm gave significantly higher seed cotton yield (1666 kg ha-1) and maximum uptake of NPK and higher gross returns, net returns and benefit cost ratio (BCR) than the other spacings tested and it was on par with 75 cm × 10 cm. The highest seed cotton yield and maximum uptake of NPK and higher gross returns, net returns and benefit- cost ratio was recorded with a nitrogen level of 150 kg N ha-1 (1620 kg ha-1) than other nitrogen levels tested.